Effect of Peritoneal Lavage with Coconut Water in Healing of Colon Anastomosis in Rat Abdominal Sepsis Model - Pires, Bárbara Bruna de Sousa; Azevedo, Italo Medeiros; Moreira, Marília Daniela Ferreira de Carvalho; Celani, Lívia Medeiros Soares; Medeiros, Aldo Cunha (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2017)
Purpose: The objective of this study was to evaluate the efficacy of peritoneal lavage with coconut water in the healing of colonic anastomoses in a model of abdominal sepsis in rats. Methods: Twelve Wistar rats were used. The animals were randomly selected and distributed in 2 groups, with six rats each. Group 1: rats with sepsis + peritoneal lavage with 0.9% saline solution and Group 2: rats with sepsis + peritoneal lavage with coconut water. Induction of abdominal sepsis was performed through the exteriorization of the cecum and ligature. After ligation, 4 perforations and gentle pressure were made in the cecum, allowing the small amount of stool to escape. The cecum was then replaced in the abdominal cavity and the abdominal incision sutured. Six hours after induction of sepsis, under anesthesia in all animals, 2 cm of colon resection and anastomosis were performed. The peritoneal lavage therapy was repeated 3 times, each wash with 5 ml of solution, which remained in the peritoneal cavity for 1 minute and then removed with sterile dry gauze. Coconut water was obtained from Cocus nucifera L specimens, with sterile technique for administration to the animals. Results: In group 2 the bursting pressure of anastomosis was 196.3±17.47 mmHg, significantly higher (p=0.001) than in the saline group, (152.8±12.31 mm/Hg). The peritoneal lavage group with coconut water presented histological scores with a significantly (p<0.001) lower inflammatory process (score 14.8±3.13) compared to the saline group (score 31.7±4.92). The count of colony forming units (CFU) in the peritoneal fluid was significantly lower (p=0.001) in the coconut water group (16.0±7.32 CFU) than in the saline group (83.5±8.62 CFU). Conclusion: The treatment of abdominal sepsis with peritoneal lavage using coconut water positively afluenced the healing of colon anastomosis in rats. It favored the bursting pressure, the reduction of inflammatory process, and bacterial colonization.